Drug-Induced Gingival Overgrowth: The Effect of Cyclosporin A and Mycophenolate Mophetil on Human Gingival Fibroblasts - Dorina Lauritano; Giulia Moreo; Luisa Limongelli; Annalisa Palmieri; Francesco Carinci (Biomedicines, 2020)
Drug-induced gingival overgrowth may occur after a chronic administration of three classes of systemic drugs: Anticonvulsants, immunosuppressants, and calcium channel blockers. This study aimed to investigate how cyclosporin A and mycophenolate mophetil (immunosuppressive drugs) could interfere with human gingival fibroblasts functions, leading to gingival enlargement. Human gingival fibroblasts derived from the tissue of a 60-year-old female were cultured in a DMEME medium. A stock solution with 1 mg/mL of mycophenolate and 1 mg/mL of cyclosporine were prepared and dissolved in a DMEM medium to prepare a serial dilution at the concentrations of 5000, 2000, 1000, 500, and 100 ng/mL, for both treatments. Cell viability was measured using the PrestoBlue™ Reagent Protocol. Quantitative real-time RT-PCR was performed in order to analyze the expression of 57 genes coding for gingival fibroblasts “Extracellular Matrix and Adhesion Molecules”. Mycophenolate and cyclosporine had no effect on fibroblast cell viability at 1000 ng/mL. Both the treatments showed similar effects on the expression profiling of treated cells: Downregulation of most extracellular matrix metalloproteases genes (MMP8, MMP11, MMP15, MMP16, MMP24) was assessed, while CDH1, ITGA2, ITGA7, LAMB3, MMP12, and MMP13 were recorded to be upregulated in fibroblasts treated with immunosuppressive drugs. It has been demonstrated that gingival overgrowth can be caused by the chronic administration of cyclosporin A and mycophenolate mophetil. However, given the contrasting data of literature, further investigations are needed, making clear the possible effects of immunosuppressive drugs on fibroblasts.